PERANCANGAN MODEL EKONOMI INDUSTRI KREATIF (MEI-KRAF) MENGGUNAKAN ALGORITMA GENETIKA - Hermawan Prasetya; Yeti Widyawati (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2017)
Creative industries has been targeted to contribute more significant in 2025. In supporting this target, a prediction model should be developed. Genetic Algorithm (GA) was employed to enhanced previous simulation model of creative industries. By employing GA, the model could seek optimum investment combination for six sub sectors of creative industries.